1994
DOI: 10.1056/nejm199403033300903
|View full text |Cite
|
Sign up to set email alerts
|

Loss of The Normal NF1 Allele from the Bone Marrow of Children with Type 1 Neurofibromatosis and Malignant Myeloid Disorders

Abstract: These data provide evidence of NF1 may function as a tumor-suppressor allele in malignant myeloid diseases in children with NF-1 and that neurofibromin is a regulator of ras in early myelopoiesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
193
1
6

Year Published

1994
1994
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 412 publications
(203 citation statements)
references
References 38 publications
3
193
1
6
Order By: Relevance
“…In a review of children with NF-I and myeloproliferative disease, Shannon et al (1992) found that inheritance of NF-1 was maternal in 16 (76%) and paternal in five (24%) of 21 cases: for JCML alone the proportions were 12/17 (71%) maternal and 5/17 (29%) paternal. In our series the proportion with maternal inheritance of NF-1 was substantially lower, and the most recent series of Shannon et al (1994) contained roughly equal numbers of children with maternal and paternal inheritance.…”
Section: Methodscontrasting
confidence: 47%
See 2 more Smart Citations
“…In a review of children with NF-I and myeloproliferative disease, Shannon et al (1992) found that inheritance of NF-1 was maternal in 16 (76%) and paternal in five (24%) of 21 cases: for JCML alone the proportions were 12/17 (71%) maternal and 5/17 (29%) paternal. In our series the proportion with maternal inheritance of NF-1 was substantially lower, and the most recent series of Shannon et al (1994) contained roughly equal numbers of children with maternal and paternal inheritance.…”
Section: Methodscontrasting
confidence: 47%
“…Bader and Miller (1978) suggested that the association might be elucidated by further study of the clonal status of leukaemias in NF-1 and a search for chromosomal abnormalities. Shannon et al (1994) have recently demonstrated loss of heterozygosity of the NFI allele in the bone marrow of five out of nine children with NF-I and myelodysplasia or ANLL, indicating that NFI acts as a tumour suppressor in myeloid cells. Cytogenetic studies were available for review in a disappointingly low proportion of patients in the present study, though this is partly a reflection of the length of time since the earliest cases were diagnosed, and with improvements in cytogenetic methodology much better information would be expected from a prospective study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…RB and APC, or because the haploinsu ciency of the tsg is incomplete. It may be that NF1 ®ts the latter category, at least for some tumour types (Jacks et al, 1994;Shannon et al, 1994). (2) The weaker the selective advantage conferred by the loss, and the later in the course of tumour development, the less opportunity there will be for homozygous loss.…”
mentioning
confidence: 99%
“…Leukemic cells from NF1 patients have loss of heterozygosity for the NF1 gene [62], but do not have activating Ras mutations, in contrast with many non-NF1-associated myeloid malignancies [63]. Increased levels of Ras-GTP are found in the NF1-associated leukemias [64] and the leukemic cells show hypersensitivity to GM-CSF [65] and other cytokines [66].…”
Section: Leukemiamentioning
confidence: 99%